Trends in delivery with no one present in Nigeria between 2003 and 2013 - Austin A; Fapohunda B; Langer A; Orobaton N (Dove Medical Press, 2015)
Anne Austin,1 Bolaji Fapohunda,2,3 Ana Langer,1 Nosakhare Orobaton2,3 1Maternal Health Task Force, Harvard TH Chan School of Public Health, Boston, MA, USA; 2John Snow, Inc., Boston, MA, USA; 3USAID Targeted States High Impact Project, Washington, DC, USA Purpose: Skilled attendance at birth is a proven intervention to improve maternal and newborn health outcomes. Unfortunately, in Nigeria there are many women who give birth alone, with no one present (NOP). The purpose of this study was to document trends in women delivering with NOP between 2003 and 2013, and to identify the characteristics of women who are engaging in this risky practice.Methods: We utilized pooled data sets from the 2003, 2008, and 2013 Nigerian Demographic and Health Surveys. Married women, who had given birth in the 5 years before each survey were included, resulting in a sample size of 38,949 women. We used logistic regression to assess the unadjusted and adjusted odds of a woman delivering with NOP over time, by sociodemographic characteristics.Results: Prevalence of delivery with NOP in Nigeria declined by 30% between 2003 and 2013. The largest declines occurred in Sokoto State, where the number of women giving birth with NOP declined by almost 100% between 2003 and 2013. In the North West of the country, however, there was a 27% increase in the number of women giving birth alone over this time period. Older, poorer, less educated, higher parity, Muslim women residing in the Northern regions were significantly more likely to give birth with NOP. Women, who were involved in decisions surrounding their own health, and who had accessed antenatal care were significantly less likely to give birth with NOP.Conclusion: Although there have been improvements in Nigeria’s Maternal Mortality Ratio since 1990, recent estimates suggest a stagnation in this trend. One reason for this protracted decline may be lack of access to skilled delivery care. The 2013 national prevalence of Nigerian women giving birth with NOP was 14%, equivalent to over 1 million births in 2013. Nigeria must implement interventions to ensure every woman’s timely access to, and use of skilled care to reduce preventable maternal mortality and morbidity.Keywords: skilled birth attendance, delivery with no one present, maternal mortality, facility-based delivery, health care seeking behaviors, Nigeria